IgG4‐related disease in asbestos‐related pleural disease. Issue 1 (30th December 2015) - Onishi, Yasutaka; Nakahara, Yasuharu; Hirano, Katsuya; Sasaki, Shin; Kawamura, Tetsuji; Mochiduki, Yoshiro
Abstract: A 67‐year‐old man with a history of asbestos exposure and rounded atelectasis complained of cough and swelling in the left submandibular region. Computed tomography showed an increase in size of the right lower lung lobe lesion, which was recognized as the pre‐existing rounded atelectasis, as well as swelling of the pancreas and submandibular glands. Biopsy from a submandibular gland and the pulmonary lesion led to a diagnosis of immunoglobulin G4‐related disease (IgG4‐RD). IgG4‐RD is a recently recognized disease that was first reported as an autoimmune disease; however, some reports have indicated another pathogenesis of an allergic nature that is characterized by type 2 helper T cell (Th2) inflammation. Additionally, it is recognized that long‐term exposure to asbestos can cause immune dysregulation. Here we present a case of IgG4‐RD associated with asbestos‐related pleural disease. Asbestos‐induced immune dysregulation may be one etiology of IgG4‐RD. Abstract : IgG4‐RD is a recently recognized disease that was first reported as an autoimmune disease, however, some reports have indicated another pathogenesis. Here we present a case of IgG4‐RD associated with asbestos‐related pleural disease (ARPD). Asbestos‐induced immune dysregulation may be one etiology of IgG4‐RD.